2016
DOI: 10.1002/jat.3390
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of metal salts at sub‐toxic concentrations

Abstract: Because different metals are used in complementary medicine for the treatment of diseases related to a dysfunction of the immune system, this study aimed at determining the immunomodulatory potential of Pb(NO ) , AuCl , Cu(NO ) , HgCl , AgNO , SnCl , AsCl and SbCl at sub-toxic concentrations and at assessing possible toxic side effects of low-concentrated metal preparations. The influence of the metal salts on primary human mononuclear cells was analyzed by measuring cell viability using the water-soluble tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…At present, the effect of arsenic on it is currently controversial. Although most studies believe that arsenic has immunosuppressive effects [ 24 26 ], there are also studies that suggest arsenic could be used as an immune stimulant to induce allergic reactions and autoimmune diseases [ 5 , 27 29 ]. Immune regulation is necessary to control the occurrence and development of inflammation and autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the effect of arsenic on it is currently controversial. Although most studies believe that arsenic has immunosuppressive effects [ 24 26 ], there are also studies that suggest arsenic could be used as an immune stimulant to induce allergic reactions and autoimmune diseases [ 5 , 27 29 ]. Immune regulation is necessary to control the occurrence and development of inflammation and autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, excessive Cu-fortification of LF might lead to decreased anti-inflammatory activity in the stimulated macrophages. Although Cu is very important to the immune system, it was also found that higher Cu levels led to an immuno-suppressive effect on the primary human mononuclear cells ( Steinborn et al, 2017 ). It is thus reasonable that LF-Cu-20 had lower anti-inflammatory activity than LF-Cu-10 in the stimulated cells.…”
Section: Discussionmentioning
confidence: 99%
“…The immunoregulatory effect of intracellular copper metabolism has been examined in several studies (Videla et al, 2003;Steinborn et al, 2017;Zhao and Zhao, 2019). Deigendesch et al (2018) found that depriving intracellular copper transporters of copper ions inhibited inflammasome activation in macrophages, thereby regulating the immune phenotype of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Low-concentration copper preparations have been reported to have promising immunomodulatory potential and to contribute to oxidative stress in macrophages (Videla et al, 2003;Steinborn et al, 2017;Zhao and Zhao, 2019). Mitochondrial-derived reactive oxygen species (mtROS) are believed to derive mainly from NADH dehydrogenase when there is a high NADH/NAD+ ratio in the mitochondrial matrix.…”
Section: High Levels Of Mitochondrial-derived Reactive Oxygen Species Might Enhance Ccm-promoted Expression Of Pdgf-bb By M2a Macrophagesmentioning
confidence: 99%